OPTIMIZATION OF DETOXICATING INFUSION THERAPY IN ODONTOGENOUS OSTEOPHLEGMONS - Ткаченко, П.І.; Гуржій, О.В.; Білоконь, С.О.; Коротич, Н.М. (World of Medicine and Biology, 2015)
The efficiency of “Rheosorbilact” detoxification activity in a comparative perspective in the complex treatment of acute odontogenic osteomyelitis, complicated by maxillofacial phlegmons involving 2-3 adjacent anatomical regions or celluloses spaces. Established the dynamic changes in the development of endogenous intoxication, depending on the amount of therapeutic interventions in 37 children 7-12 years of age, who were divided into two groups. In 20 of them the composition of pharmaceutical preparations included a list of corresponding base method, and in the other group, consisting of 17 children in the complex was additionally introduced “Reosorbilact”. The survey revealed that markers of endogenous intoxication levels on the 5th day of observation were lower was in the second group of patients, indicating a more severe detoxification properties of the plasma-drug.